Pengembangan Modul Kewirausahaan Berbasis Succes Story Upaya Menumbuhkan Intensi Berwirausaha Mahasiswa Program Studi Pendidikan Ekonomi - Rapii, Muhammad; Juani, Muhamad (Universitas Hamzanwadi, 2017)
This research aims to develop entrepreneurship module based on succes story in an effort to grow student entrepreneurship intent of economic education. Therefore, the steps of developing entrepreneurial modules based on this success story refer to the development of learning from Dick and Carey.Discussion of research using research development model (research and development). which consists of ten steps, namely: 1) perform needs analysis; 2) malakukan learning analysis; 3) analyzing learners and the context; 4) outline general goals into more specific objectives; 5) develop assessment instruments; 6) developing learning strategies; 7) developing and selecting learning materials; 8) design and perform formative evaluation; 9) make revisions; 10) conduct summative evaluation.The results of the study indicate that the assessment of the expert of the field of study, the designer of the lesson and the linguist to the result of the development of entrepreneurship module based on succes story is feasible to be used. The product component of entrepreneurship module development is based on a success story that has been piloted through five stages and revisions, to the lecturer in the field of study, the design expert of the lesson and the linguist, where the result of the assessment is a good average. The result of the development of entrepreneurship module based on succes story can improve student entrepreneurship intention.